Advances in narrow linewidth and wide tuning range external-cavity wavelength-swept lasers - Sheng, Liwen; Wang, Jianjun; Huang, Lin; Zhang, Aiguo; Zhang, Zhihui; Qiao, Shan; Wei, Yu; Liu, Zhiming; Ju, Junwei; Zhou, Shuai; Liu, Jiaqing; Han, Jilei; et al. (Frontiers in Physics, 2024)
An external-cavity wavelength-swept laser, characterized by its exceptional temporal coherence and extensive tuning range, serves as a crucial light source for cutting-edge fields such as fiber sensing, lidar, and spectroscopy. The burgeoning growth of optical communication technology has escalated the demand for lasers with narrow linewidth and broad tuning range, thereby catalyzing the swift advancement of external-cavity wavelength-swept diode lasers and their diverse applications. This article comprehensively presents the configurations and operating principles of these lasers, and provides an in-depth review of their development status, specifically focusing on those with narrow linewidth and wide tuning range. The aim is to offer a valuable reference for researchers involved in the development and application of wavelength-swept lasers.